Femisida Perspektif Kesetaraan Gender dan Hukum Islam - Ash Shiddiqi, Hasbi (USRATUNA: Jurnal Hukum Keluarga Islam, 2025)
Femicide, or the murder of women due to gender, is a global phenomenon that requires special attention in the context of Islamic family law. This article aims to analyze femicides through a normative and sociological approach, focusing on women's rights as stipulated in Islamic family law. This research uses a qualitative method with a descriptive-analytical approach, utilizing literature studies on primary sources such as the Qur'an, hadith, and fiqh books, and secondary data in the form of contemporary research related to the issue of femicides. The results of the study show that Islamic family law fundamentally emphasizes the protection of women through the principles of justice, protection of life (Hifz al-Nafs), and respect for human rights. However, challenges arise in the implementation of these laws, especially due to patriarchal cultural bias that is still dominant in some Muslim communities. From a sociological point of view, femicides often occur due to gender power imbalances, weak understanding of Islamic legal principles, and lack of fair law enforcement. The significance of this research lies in its efforts to reconstruct the perspective of Islamic family law in preventing and dealing with femicides. This article offers recommendations to improve public understanding of women's rights in Islam, strengthening regulations that are in line with maqasid syariah, and encourage legal reform to bring about gender justice. Thus, this research makes an academic as well as practical contribution in the development of Islamic family law that is responsive to contemporary issues.